On the relationship between speech and writing with implications for behavioral approaches to teaching literacy - Moxley, Roy A. (1990)
Two theories of the relationship between speech and writing are examined. One theory holds that writing is restricted to a one-way relationship with speech—a unidirectional influence from speech to writing. In this theory, writing is derived from speech and is simply a representation of speech. The other theory holds that additional, multidirectional influences are involved in the development of writing. The unidirectional theory focuses on correspondences between speech and writing while the multidirectional theory directs attention to the differences as well as the similarities between speech and writing. These theories have distinctive pedagogical implications. Although early behaviorism may be seen to have offered some support for the unidirectional theory, modern behavior analysis should be seen to support the multidirectional theory.